Microwave assisted synthesis of new curcumin analogues conjugated dihydro-4-pyridones - Aboud, Maitham Najim; Saeed, Bahjat Ali; Elias, Rita Sabah (European Journal of Chemistry, 2015)
New curcumin analogues, conjugated dihydro-4-pyridones were synthesized via reaction of curcumin with primary amines or amine acetates under microwave irradiation. Montmorillonite K-10 was used as a catalyst and reaction times within the period 60-90 s. The synthesized compounds were characterized on the basis of their IR, UV-Vis, 1H, 13C NMR and mass spectra.